Innovative Learning Strategies for Optimizing Literacy Competencies in Elementary Indonesian Language Instruction: A Systematic Literature Review - Nabila, Ulianandha Putri; Istiq’faroh, Nurul; Sukartiningsih, Wahyu (Journal of Innovation and Research in Primary Education, 2025)
Low literacy competencies among Indonesian elementary students, as evidenced by international assessments, necessitate innovative pedagogical approaches. This study examines learning strategies for optimizing literacy skills in Indonesian language instruction at the elementary level. A systematic literature review was conducted across multiple databases (Google Scholar, ERIC, ScienceDirect) covering publications from 2018-2024. Five empirical studies meeting rigorous inclusion criteria were analyzed using thematic synthesis to identify effective strategies and their characteristics. Five pedagogical approaches demonstrated significant effectiveness: Cooperative Integrated Reading and Composition (CIRC) enhanced critical thinking and comprehension; Project-Based Learning (PJBL) developed linguistic and non-linguistic competencies; Problem-Based Learning (PBL) promoted higher-order thinking skills; Deep Learning through multiliteracy pedagogy enabled differentiated instruction; and Contextual Teaching and Learning (CTL) improved reading comprehension through contextual relevance. All strategies emphasized active engagement, collaborative learning, and authentic task integration, yielding substantial improvements in reading, writing, and critical thinking abilities compared to conventional instruction. These findings align with constructivist learning theory and strongly support Kurikulum Merdeka principles of student-centered, differentiated instruction. The convergence of positive outcomes across diverse strategies provides evidence-based guidance for educators while highlighting the need for comprehensive teacher professional development and systemic institutional support for sustainable implementation.